A qualitative process evaluation of SBIRT implementation in pediatric trauma centers using the Science to Service Laboratory implementation strategy - Kelli Scott; Michael J. Mello; Geraldine Almonte; Emely Arenas Lemus; Julie R. Bromberg; Janette Baird; Anthony Spirito; Mark R. Zonfrillo; Karla Lawson; Lois K. Lee; Emily Christison-Lagay; Stephanie Ruest; et al. (Implementation Science Communications)
Abstract Background Screening, Brief Intervention, and Referral to Treatment (SBIRT) is an evidence-based practice that can identify adolescents who use alcohol and other drugs and support proper referral to treatment. Despite an American College of Surgeons mandate to deliver SBIRT in pediatric trauma care, trauma centers throughout the United States have faced numerous patient, provider, and organizational level barriers to SBIRT implementation. The Implementing Alcohol Misuse Screening, Brief Intervention, and Referral to Treatment Study (IAMSBIRT) aimed to implement SBIRT across 10 pediatric trauma centers using the Science-to-Service Laboratory (SSL), an empirically supported implementation strategy. This manuscript aimed to assess trauma center staff preferences and experience with the didactic training, performance feedback, and ongoing coaching elements of the SSL via a retrospective qualitative process evaluation. Methods Nurses, social workers, and site leaders that participated in IAMSBIRT were recruited to complete qualitative exit interviews guided by the Consolidated Framework for Implementation Research. Qualitative interviews were recorded, transcribed, and analyzed by two coders using a directed content analysis approach in NVivo software. Codes were then translated into frequently endorsed themes by the IAMSBIRT study research team. Results Thirty-six exit interviews were conducted with site leaders, social workers, and nurses across the 10 IAMSBIRT pediatric trauma centers. Findings revealed key strengths as well as areas for improvement across the IAMSBIRT preparation phase and the three elements of the SSL: didactic training, performance feedback, and ongoing coaching. Trauma center staff generally reported that all three elements of the SSL were high quality and helpful for supporting SBIRT implementation. However, staff also noted that performance feedback and ongoing coaching were generally only available to center leadership or to individuals selected by leadership, making it challenging for non-leaders to troubleshoot SBIRT delivery. Conclusions Findings from the qualitative process evaluation revealed discrepancies in the experience of the SSL strategy between those in leadership roles and those involved in direct care delivery. These results suggest the need for several modifications to the SSL strategy, including increasing engagement of direct care staff in all elements of the SSL throughout the implementation process. Trial registration Clinicaltrials.gov NCT03297060 . Registered 29 September 2017.